Desat.se: produção jornalística sobre saúde mental em perspectiva transmidiática - Reis, Marcos Vinícius (2020)
The development of the Internet and the emergence of a convergence culture have engendered a model of production, distribution and consumption of content aligned with the economic interests of large media conglomerates, especially those linked to the entertainment industry: the transmedia storytelling. Researchers in the field of communication have pointed to the potential of the combination of transmedia and journalism, and, although experiments in this regard are still scarce, they are promising. In this work, we aim to experimentally develop a transmedia journalistic production on mental health, entitled “desat.se”, crossed by formats and genres that comprise longform journalism, literary journalism and comics journalism, and composed of a website and a user community (social media groups Facebook and WhatsApp, an Instagram page and a crowdfunding page on “APOIA.se” platform). We applied, methodologically, the transmedia project design analytical model by Gambarato and Dabagian (2016) as a tool for planning and building the proposal. "Desat.se" emphasizes the collaboration of users in the composition of the content, seeking to take advantage of the creative and economic possibilities unveiled by the convergence culture and by the current migratory behavior of audiences, who transit through different media. With this work, we intend to contribute to the development of research in the area, emphasizing, above all, the possible intersections between transmedia storytelling and journalism.